Bis{2 '- (5-chloro-1H-3-indolyl)methylene 2-(1H-3-indolyl)acetohydrazido-kappa N-2,O}nickel(II) dimethyl sulfoxide disolvate - Ali, Hapipah Mohd; Ng, S.W.; Rizal, M.R.; Nazzatush, J. (International Union of Crystallography, 2007)
The Ni atom in the title compound, [Ni(C19H14ClN4O)(2)]center dot 2C(2)H(6)OS, which lies on a centre of inversion, is N, O-chelated by the two monoanionic ligands in a square-planar geometry. The asymmetric unit also contains a dimethyl sulfoxide solvent molecule. The donor amino sites of the metal-bearing molecule interact with the solvent molecules to furnish a hydrogen-bonded layer structure.